Neural Correlates of Cognitive-Attentional Syndrome: An fMRI Study on Repetitive Negative Thinking Induction and Resting State Functional Connectivity - Kowalski, Joachim; Wypych, Marek; Marchewka, Artur; Dragan, Małgorzata (Frontiers in Psychology, 2019)
Aim: Cognitive-attentional syndrome (CAS) is the main factor underlying depressive and anxiety disorders in the metacognitive approach to psychopathology and psychotherapy. This study explored neural correlates of this syndrome during induced negative thinking, abstract thinking, and resting states. Methods: n=25 people with high levels of CAS and n=33 people with low levels of CAS were chosen from a population-based sample (N=1225). These groups filled-in a series of measures of CAS, negative affect, and psychopathology; they also underwent a modified rumination induction procedure and a resting fMRI scan. Resonance imaging data were analysed using static general linear model and functional connectivity paradigms. Results: The two groups differed with large effect sizes on all used measures of CAS, negative affect, and psychopathology. We did not find any group differences in general linear model analyses. Functional connectivity analyses showed that high levels of CAS were related to disrupted patterns of connectivity within and between various brain networks: the default mode network, the salience network, and the central executive network. Conclusions: We showed that low- and high-CAS groups differed in functional connectivity during induced negative and abstract thinking and also in resting state fMRI. Overall, our results suggest that people with high levels of CAS tend to have disrupted neural processing related to self-referential processing, task-oriented processing, and emotional processing.